RESPON POLANDIA TERHADAP EUROPEAN GREEN DEAL (EGD) - Putri, Ayuda Lestika; Olivia, Yessi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research explains the response of Poland, a member state of the European Union (EU),to the European Green Deal (EGD), which was introduced by the European Commission in 2019. The EGD is a climate agreement consisting of a series of initiatives aimed at making Europe the first carbon-neutral region by 2050. This research is a qualitative research that uses with the rational actor model in foreign policy decision making to analyze Poland’s response to the EGD. The level analysis used in this research was the state level. The data collection used in this research is a document analysis method which was reviewed throught from several books, documents, journal articles, and other relevant references to Poland’s response to the EGD. Research shows that Poland had considered various aspects such as economics, history, geography, and social in responding to the EGD. Poland had also provided its views on the EGD at meetings of EU leaders. By considering many aspects, Poland’s response to the EGD is to agree to some of the points in the EGD that are tailored to the country’s conditions. Keywords: Response, Poland, EU, EGD.